ACTIONS REGARDING INCREASING OF EFFICENCY OF ELECTRIC NETWORK - Gritsai M. (Problems of the Regional Energetics, 2011)
The retrospective analysis of losses of energy in the electrical network of several institutions of the Academy of Sciences of Moldova is executed. On the basis of the data of the power consumption for year 2010 losses of energy in all elements of the network are calculated. As a result of calculation is revealed: (1) the established capacity of transformers is superfluous concerning level of the power consumption, (2) transformers are loaded on the average on 17 % f, (3) in structure of losses the basic share (97 %) is made with losses in steel of transformers. The new configuration of a network is offered in which: (i) six (6) transformers are disconnected from a network, (ii) on the side 0.4 kV are established additional electric connections between the disconnected and working transformers, (iii) loading of the disconnected transformers is moved to the working transformers, (iv) the former level of reliability of electricity supply is kept. In the offered network of losses are reduced on 55000 kWh, that gives economy about 100000 MDL in year.